3(w+1)=5w-1

Simple and best practice solution for 3(w+1)=5w-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(w+1)=5w-1 equation:


Simplifying
3(w + 1) = 5w + -1

Reorder the terms:
3(1 + w) = 5w + -1
(1 * 3 + w * 3) = 5w + -1
(3 + 3w) = 5w + -1

Reorder the terms:
3 + 3w = -1 + 5w

Solving
3 + 3w = -1 + 5w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-5w' to each side of the equation.
3 + 3w + -5w = -1 + 5w + -5w

Combine like terms: 3w + -5w = -2w
3 + -2w = -1 + 5w + -5w

Combine like terms: 5w + -5w = 0
3 + -2w = -1 + 0
3 + -2w = -1

Add '-3' to each side of the equation.
3 + -3 + -2w = -1 + -3

Combine like terms: 3 + -3 = 0
0 + -2w = -1 + -3
-2w = -1 + -3

Combine like terms: -1 + -3 = -4
-2w = -4

Divide each side by '-2'.
w = 2

Simplifying
w = 2

See similar equations:

| 47x+149=133 | | 3w+6=-w+30 | | -1/2X=-10 | | 4*(2-3x)-2*(9x-8)=15*(1-x)+3*(4-x) | | 6f+1=2f+13 | | 4x-35=x+12 | | 4=-3+6 | | 7x+12=-4 | | 3x^2=4-11x | | (-23-32)0.56=c | | 9n-2=7n+40 | | (e^6x)+(4e^3x)-12=0 | | 6x+18=-2x+-62 | | -16x^2+75x+4=0 | | 7(3n+1)=-161 | | (120-32)0.56=c | | 6x+18=-2x+31 | | -2x+9=-3 | | (97-32)0.56=c | | 3n-5=12 | | 5*(0,14-0,23x)+3*(0,3x+0,1)=0 | | 3ln(7x)=27 | | 0.04(6000-x)=300 | | x^2+4x+2ix+2i+3=0 | | -1/2(8x+2)+1/5(35+10)= | | 3*ln(7x)=27 | | 3/8*2/3*3/4 | | 4*(0,6x-0,3)-3*(0,7x-0,1)=0 | | [2x-1]=2 | | -6x-3(7x-26)=-11 | | 14u-8+6u+41= | | -288=2x-6(6x-20) |

Equations solver categories